PERKEMBANGAN HIV/AIDS DAN PENYAKIT INFEKSI MENULAR SEKSUAL TAHUN 2022 - Fajar Maghda; Cicih Indah Rahayu, Sheren Yolanda Viska, Prapti Setyaningsih, Eva Mardiana, Riza Fahlapi (Jurnal Kesehatan, 2025)
The research reviews recent developments in epidemiology, clinical management, health policy, and prevention eflorts globally and in Indonesia. The research utilizes a literature review method and secondary data analysis from various reliable sources, including reports from WHO, CDC and the Indonesian Ministry of Health. The results show that despite significant advances in treatment and prevention, major challenges remain. Social stigma, unequal access to health services, and lack of education remain major barriers to HIV/AIDS and STD treatment. The year 2022 also saw the emergence of new innovations in health-related Sustainable Development Goals (SDGS) therapy. This concludes that the successful management of HIV/AIDS and STDs requires a multifaceted approach that includes improving education, strengthening health systems, and cross-sectoral cooperation. Recommendations include developing more inclusive prevention programs, improving access to health services, and reducing stigma through public awareness campaigns.